Fanatisme pada suporter bola: Menguji penanan kematangan emosi - Hafizh harmawan; Adnani Budi Utami; Hetti Sari Ramadhani (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine the relationship between emotion and fanaticism in football fans. This research is a type of quantitative research using correlational research. The subjects in this study were 66 respondents from the Tanjungsari Bonek Community who were selected through a non-random sampling technique, namely purposive sampling. The data analysis technique used in this study is the Spearman Rho technique. The results show that there is a relationship with a correlation negative and very significant relationship between emotional maturity and fanaticism. This means that the higher the emotion, the lower the fanaticism, the lower the emotion, the higher the fanaticism. The results of the study are expected to be a lesson to reduce the behavior of negative fanaticism in football fans. Keywords: Emotional Maturity; Fanaticism; Supporters.